2007
DOI: 10.1200/jco.2006.08.8005
|View full text |Cite|
|
Sign up to set email alerts
|

Quality of Life in Head and Neck Cancer Patients After Treatment With High-Dose Radiotherapy Alone or in Combination With Cetuximab

Abstract: The addition of cetuximab to radiotherapy significantly improved locoregional control and increased overall survival without adversely affecting QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
116
1
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(139 citation statements)
references
References 31 publications
13
116
1
9
Order By: Relevance
“…[2][3][4][5][6][7][8][9] This may be due to perceptions that radiation, particularly for T4 bony lesions, is an ineffective modality for advanced OCC. In addition, it is generally thought that radiation doses that would be considered therapeutic for advanced OCC would lead to unacceptable toxicities in the form of xerostomia, or radiation-induced soft-tissue or bone necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] This may be due to perceptions that radiation, particularly for T4 bony lesions, is an ineffective modality for advanced OCC. In addition, it is generally thought that radiation doses that would be considered therapeutic for advanced OCC would lead to unacceptable toxicities in the form of xerostomia, or radiation-induced soft-tissue or bone necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that the synergistic effect of gemcitabine and anti-EGFR medication results from the fact that the latter is inhibiting EGFR phosphorylation and blocking the initial survival response (EGFR activation) induced by gemcitabine and thereby promoting apoptosis. Cetuximab/ radiotherapy, because of its assumed better tolerance and compliance [72,73], often serves as an alternative for cisplatinbased CCRT in patients who might have difficulties tolerating it, albeit that a recent literature-based meta-analysis suggested inferior efficacy [74]. As the addition of cetuximab to platinumbased CCRT only adds toxicity to platinum-based CCRT without increasing efficacy [75], other cytotoxic agents with less systemic toxicity and with a different mode of action, such as gemcitabine, in combination with cetuximab and radiation, are an interesting field of research.…”
Section: Discussionmentioning
confidence: 99%
“…Bonner et al,19, 20 in their prospective randomized trial, compared RT‐alone with RT plus cetuximab and reported improvement in locoregional control and survival with no significant increase in toxicity. Short‐term QOL between the two arms was also similar 21. In a retrospective study comparing concurrent cisplatin and RT with cetuximab and RT for LAHNC, concurrent cisplatin achieved better local control and survival but there was no significant difference in late Gr3 or Gr4 effects or feeding tube dependence 22, 23.…”
Section: Discussionmentioning
confidence: 69%